1993
DOI: 10.1115/1.2910189
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow in the Obstructed Space Between Disks Corotating in a Cylindrical Enclosure

Abstract: Time-resolved measurements of the circumferential velocity component were obtained with a laser-Doppler velocimeter in the space between the center pair of four disks corotating in air in an axisymmetric cylindrical enclosure. The separate influences on the flow of two obstructions of similar shapes but having different lengths were investigated. The results show that both obstructions significantly alter the mean and rms distributions of velocity in quantitatively different but qualitatively similar ways. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…They primarily reported mean and RMS values of circumferential velocities and the corresponding frequency content. Usry et al [9] also conclude that once the flow separates by flowing over the obstruction, "the flow does not recover within one revolution from the effects of the obstruction. "…”
Section: A Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…They primarily reported mean and RMS values of circumferential velocities and the corresponding frequency content. Usry et al [9] also conclude that once the flow separates by flowing over the obstruction, "the flow does not recover within one revolution from the effects of the obstruction. "…”
Section: A Prior Researchmentioning
confidence: 99%
“…10, the flow field is similar to M0, except that the upstream spoiler acts as another source of generation of turbulent eddies. The eddies shed from the top and bottom edges cause added velocity fluctuations in the upstream portion of the flow field (see (9) in Fig. 10).…”
Section: A Major Flow Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a laser Doppler velocimeter (LDV) technique, Usry et al (1993) obtained the circumferential velocity and corresponding RMS for the flow within a pair of corotating disks enclosed by a cylindrical shroud. Two obstructions geometrically similar with a taper toward the rotating center, but having different lengths were used.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by Abrahamson et al [3,4] revealed that the flow structures generated by the arm are dissipated in a short circumferential distance in the wake of arm. Usry et al [5] observed that the presence of an arm reinforces the cross-stream secondary flow in the radial direction. Gross [6] reported that the profile of arm leading edge has a significant effect on the flow velocity fluctuations measured in the vicinity of arm tip.…”
Section: Introductionmentioning
confidence: 99%